"Ballistic Six" upper-extremity plyometric training for the pediatric volleyball players - Turgut, E.; Cinar-Medeni, Ö.; Colakoglu, F. F.; Baltaci, G. (The Journal of Strength and Conditioning Research, 2019)
The Ballistic Six exercise program includes commonly used upper-body exercises, and the program is recommended for overhead throwing athletes. The purpose of the current study was to investigate the effects of a 12-week the Ballistic Six upper-extremity plyometric training program on upper-body explosive power, endurance, and reaction time in pediatric overhead athletes. Twenty-eight female pediatric volleyball players participated in the study. The participants were randomly divided into 2 study groups: an intervention group (upper-extremity plyometric training in addition to the volleyball training; n = 14) and a control group (the volleyball training only; n = 14). All the participants were assessed before and after a 12-week training program for upper-body power, strength and endurance, and reaction time. Statistical comparison was performed using an analysis of variance test. Comparisons showed that after a 12-week training program, the Ballistic Six upper-body plyometric training program resulted in more improvements in an overhead medicine ball throwing distance and a push-up performance, as well as greater improvements in the reaction time in the nonthrowing arm when compared with control training. In addition, a 12-week training program was found to be effective in achieving improvements in the reaction time in the throwing arm for both groups similarly. Compared with regular training, upper-body plyometric training resulted in additional improvements in upper-body power and strength and endurance among pediatric volleyball players. The findings of the study provide a basis for developing training protocols for pediatric volleyball players.